Myopic Loss Aversion dan Literasi Keuangan Pada Pengambilan Keputusan Investor Pemula Indonesia - Andi Fauziah; Budi Purwanto; Wita Juwita Ermawati (Jurnal Manajemen dan Organisasi, 2020)
Risk averse behavior are psychological barriers for investor to join the capital market. Risk averse behavior will restrict the investor financial decision, so it needs to be anticipated through improving financial literacy. Low financial literacy increases the evaluation frequency, hence the risk averse behavior will increased and reduce the return. This problem can be prevented by increasing financial literacy so that the investor will behave as a risk seeker and increase the return. This paper aims to examine factors that are affected the investor returns. Multiple linear regression analyses using SPSS 20 was utilized to see the effect of financial literacy, evaluation frequency, maxhold, investment duration, technical analysis, and fundamental analysis against return increasing. The results showed that financial literacy and investment durations were positively significant towards investor returns, the use of technical analysis negatively significant towards investor returns, while insufficient evidence to Indicates that the frequency of evaluation, max hold, and the use of fundamental analysis affects investors returns at a 90 percent confidence level.